Road dogs [compact disc, unabridged] - Leonard, Elmore, 1925-2013 (Harper Audio, 2009)
The refined bank robber Jack Foley is back again, along with two other illustrious characters: Dawn Navarro, a gorgeous psychic, and Cuando Rey, a rich Cuban refugee. Here, Foley gets nabbed by the police during a routine robbery and is sentenced to 30 years in prison.